4y + 3 ≤ y + 6
4y + 3 - 3 ≤ y + 6 - 3
4y ≤ y + 3
4y - y ≤ y - y + 3
3y ≤ 3
3y/3 ≤ 3/3
y ≤ 1
So any value of y less than or equal to 1 (so 1 is included in the solution set) satisfies the inequality. C is the correct answer.
Answer:
5.2 Minutes, or 5 minutes and 12 seconds
Step-by-step explanation:
You can solve this problem by working backward. Since our number gets smaller by a 1/10 or 0.1, in order to work backward we must multiply 3.60 by 10/9, since one tenth has been taken away already. When we do this, we get 4.0. When we add 1.2 minutes to that, we get a final answer of 5.2 minutes, or 5 minutes and 12 seconds.
Answer:
Step by Step:
x-2y=4
+2y +2y
x=-2y+4
x-2y=4
-4 -4
x-2y-4=0
+2y +2y
x-4=2y
Divid by 2
1/2x-2= y
x=-2y+4
x=-2(1/2x-2)+4
x=-x+4+4
x=-x+8
+x +x
2x= 8
x=4
y=1/2x-2
y=1/2(4)-2
y=2-2
y=0
(4,0)